Variability in white blood cell count during uncomplicated malaria and implications for parasite density estimation: a WorldWide Antimalarial Resistance Network individual patient data meta-analysis - Wynberg, Elke (2023)
Andre M. Siqueira - Fundação de Medicina Tropical Dr. Heitor Vieira Dourado, Manaus, AM, Brazil / Universidade do Estado do Amazonas. Programa de Pós-graduação em Medicina Tropical. Manaus, AM, Brazil / Fundação Oswaldo Cruz. Instituto Nacional de Infectologia Evandro Chagas. Laboratório de Pesquisa Clínica em Doenças Febris Agudas. Rio de Janeiro, RJ, Brazil.